Catheter ablation of Idiopathic Ventricular Arrhythmias in Nepal-5 Years Single Centre Experience - Raut, Roshan; Dhungana, Murari; KC, Man Bahadur; Sharma, Mukunda; Joshi, Surakshya; Bajracharya, Prashanta; Sherpa, Kunjang; Pradhan, Laksheshwor; Rajbhandari, Sujeeb (Nepalese Heart Journal, 2021)
Background and Aims: Idiopathic ventricular arrhythmia (IVAs) is defined as premature ventricular complexes (PVCs), nonsustained ventricular tachycardia or sustained ventricular tachycardia (VT) in the absence of obvious structural heart disease. Catheter ablation has become an established treatment strategy for wide varieties of idiopathic ventricular arrhythmias. The aim of this study is to report the efficacy and safety of catheter ablation of idiopathic ventricular arrhythmias, for the first time in Nepal. Methods: This is a retrospective observational descriptive study of all patients who underwent electrophysiological study and radiofrequency catheter ablation for IVAs from March, 2015 to February 2020 at Shahid Gangalal National Heart center (SGNHC). Results: Altogether 101 patients underwent an EP study with intent to ablations for idiopathic ventricular arrhythmias. In 13 patients, ventricular arrhythmias were not present on the procedure day and also could not be induced in the lab, therefore ablation was performed in 88 patients only. RVOT was the most common site of these arrhythmias comprising 51% of all cases, followed by fascicular VT (34%) and basal left ventricular IVAs (15%). Out of 88 patients, the acute success of 7 patients could not be assessed because of very infrequent PVCs. Out of remaining 81 patients, acute success achieved in 77 patients (95%). Recurrence occurred in 9 patients (10.7%) and 4 patients underwent repeat ablation giving rise to over clinical success during follow up in 78 patients (88.7%). There were two major complications, one pulmonary embolism and another cardiac tamponade both managed successfully. Conclusion: This single-center single operator study demonstrates that catheter ablation of idiopathic ventricular arrhythmias has a high success and low complication rate